The quality of life in patients with multiple sclerosis – Association with depressive symptoms and physical disability: A prospective and observational study - Kołtuniuk, Aleksandra; Pawlak, Beata; Krówczyńska, Dorota; Chojdak-Łukasiewicz, Justyna (Frontiers in Psychology, 2023)
Background: Patients with multiple sclerosis (MS) experience disabilities which significantly affect their quality of life (QOL) and mental health. Mood disorders and depressive symptoms are one of the most common psychiatric conditions in MS patients. This study aimed to evaluate the level of QOL in MS patients and to assess the influence of depressive symptoms and physical disability on QOL. Methods: This prospective and observational study was conducted among 100 MS patients (mean age of 36.23 ± 11.77) recruited from the Lower Silesian Unit of the Polish Association for Multiple Sclerosis. This study used a questionnaire designed by the authors, which contained questions about sociodemographic and clinical data, as well as the following standardized questionnaires: the Activities of Daily Living questionnaire (ADL), the Instrumental Activities of Daily Living questionnaire (IADL), the Expanded Disability Status Scale (EDSS), the Beck Depression Inventory (BDI) and Multiple Sclerosis International Quality of Life Questionnaire (MusiQOL). Results: The average EDSS score among patients was 3.13 ± 2.38 points. More than half of the respondents (68%) suffered from depression of varying severity. The univariate linear regression models showed that the independent (p<0.05) QOL predictors (total MusiQOL) were as follows: the number of complaints, IADL results, BDI results, EDSS score, higher education, and material status > 2000 PLN. In addition, the multiple linear regression model showed that the BDI result was a significant predictor of QOL (p<0.005). Conclusions: Depressive symptoms significantly affect the QOL of MS patients.